What we feel and why we buy: the influence of emotions on consumer decision-making. (August 2016) - Achar, Chethana; So, Jane; Agrawal, Nidhi; Duhachek, Adam
Highlights: Emotions embedded in marketing appeals or in decision contexts influence decision-making. Consumers are influenced by emotions that are both related and unrelated to the decision. Emotions impact consumer decisions through cognitive appraisals. Abstract : Each specific emotion is associated with a set of cognitive appraisals that drives the influence of the emotion on decision-making through nuanced psychological mechanisms. We present an integrated view of the current literature on how emotions – both related and unrelated to the decision at hand – play an important role in shaping consumer decision-making. Emotions embedded in marketing stimuli influence decision-making via processes driven by cognitive appraisals. Emotions that are unrelated to the decisions influence decision-making via carried over appraisal tendencies. We present perspectives on why and under what conditions emotions serve as antecedents to decision-making, and call for future research to examine how emotional influences can both undermine and help consumer decision-making.